2014
DOI: 10.1038/ncomms6196
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen signalling in white adipose progenitor cells inhibits differentiation into brown adipose and smooth muscle cells

Abstract: Oestrogen, often via oestrogen receptor alpha (ERα) signalling, regulates metabolic physiology, highlighted by post-menopausal temperature dysregulation (hot flashes), glucose intolerance, increased appetite and reduced metabolic rate. Here we show that ERα signalling has a role in adipose lineage specification in mice. ERα regulates adipose progenitor identity and potency, promoting white adipogenic lineage commitment. White adipose progenitors lacking ERα reprogramme and enter into smooth muscle and brown ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 72 publications
3
51
0
2
Order By: Relevance
“…The underlying mechanism is probably based on TGFβ signaling which is involved in progenitor reprogramming downstream of the ERα signal pathway [51]. The authors' conclusion of that study has similarities with ours but differences still remain.…”
Section: Discussionsupporting
confidence: 67%
“…The underlying mechanism is probably based on TGFβ signaling which is involved in progenitor reprogramming downstream of the ERα signal pathway [51]. The authors' conclusion of that study has similarities with ours but differences still remain.…”
Section: Discussionsupporting
confidence: 67%
“…At the level of adipocyte development, E2 and genistein act through undetermined ER isoforms to suppress human bone marrow progenitor commitment to the adipocyte lineage that underlies visceral fat development (7). Recent work on adipose niche progenitors suggests that direct ERα action promotes subcutaneous fat development that is considered metabolically advantageous (8). TGF‐β has been implicated in the effects of E2 on both bone marrow and adipocyte niche sources of stem/progenitor cells (7, 8), but additional mechanisms are likely to be important and are poorly understood.…”
mentioning
confidence: 99%
“…Recent work on adipose niche progenitors suggests that direct ERα action promotes subcutaneous fat development that is considered metabolically advantageous (8). TGF‐β has been implicated in the effects of E2 on both bone marrow and adipocyte niche sources of stem/progenitor cells (7, 8), but additional mechanisms are likely to be important and are poorly understood. Furthermore, the functions of various ER subcellular pools that may regulate adipose progenitor differentiation are unknown.…”
mentioning
confidence: 99%
“…In contrast, work in an adipose lineage-specific ERα KO mouse model showed that ERα signaling promoted the commitment of progenitor cells to the white adipocyte lineage (Lapid et al, 2014). Other studies have also demonstrated proadipogenic effects for estrogen, although Androgen receptors are expressed at higher levels in visceralderived ASCs than scASCs, in both rats and humans (Dieudonne et al, 1995(Dieudonne et al, , 1998.…”
Section: Steroid Hormones and Sex Differencesmentioning
confidence: 99%